The Spirit of Tolerance in Islam: By Reza Shah-Kazemi (London and New York: I.B. Tauris, 2012. 165 pages.) (American Journal of Islam and Society, 2014)
This monograph challenges the notion that Islam is, at its core, an intolerantreligion. Through a careful reading of the Qur’an, the Hadith literature, andextra-canonical texts, as well as examples from history, Reza Shah-Kazemiargues that Islam is rooted in an inclusivist ethic that permeates the founda-tions of Islamic belief and practice. He provides numerous examples of howMuslims have behaved in accordance with the Islamic values of unity(tawḥīd), mercy (raḥmān), and compassion (raḥmah) elucidated in theQur’an and the Hadith, and illustrated in history from the early Islamic periodto recent centuries. This volume provides an academic and sophisticated readingof tolerance in Muslim history that is accessible to the scholar, student,and layperson interested in how Islam deals with religious minorities.The introduction begins with the proposal that Islam is, at its foundation,committed to the principle of religious pluralism. Backed by eminent thinkers,including Wilfred Cantwell Smith (d. 2000) and John Locke (d. 1704), Shah-Kazemi describes this principle in terms of the “inalienable dignity” of allhuman beings as cited in Q. 30:30 and Q. 17:70: “We have bestowed dignityon the progeny of Adam [and Eve]” (p. 12). Examples of this principle are seenin the behavior of the Prophet as well as in that of his cousin and son-in-lawAli ibn Abi Talib, individuals who, in the author’s perspective, communicatedthe rule of compassion (raḥmah) throughout their lives. At the conclusion ofthis chapter, the author suggests that this practice be revived, for it accords withwestern secular principles that are not “an expression of its own specificallyreligious traditions,” but rather a result of the intra-religious wars that accompaniedthe Reformation. Shah-Kazemi uses the rest of this volume to elucidatethis spirit, which is best expressed in Q. 49:13: “O humanity, We have createdyou male and female, and We have made you into tribes and nations in orderthat you might come to know one another” (p. 19) ...